تأثير المتغيرات الاقتصادية على مؤشرات أسواق الأوراق المالية العربية - دعاء نعمان الحسيني (PROSPECTIVE RESEARCHES, 2023)
The basic analysis focuses on many aspects starting from analysis the general economic circumstances of the state , and its effects on the capital market and then analying the circumstances of the sector of the organization that the sector it belongs to it . finally,analyzing the organization’s Circumstances itself to stand on the best organization recommends by the analysis in its investment in the Securities . The research has attempted in the first level of the fundamental analysis to explain the effects of economic’s circumstances that suround the Arab capital market which participate to database of the arab monetary funds and its impact on the prices of the company’s stocks listed in it, and through describing the standards models using the cross – sectional data for the study variables . The research summarizes of controlling the fluctuations of the prices of the local exchange rate , because the extreme fluctuations lead to change in fluctuations of indicators of the securities . Inaddition to the extension in policy to exhibit the currencies that do not lead to the increase to many investments in the scope of Shares, and many cause the investor to prefer employing the money in other fields . as it may disturb their confedence in the invested Securities .